APPLICATION OF INTERNATIONAL LEGAL STANDARDS IN UKRAINE IN THE TRANSPORT OF ANIMALS BY AIR TRANSPORT - Майстро, Діана Михайлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: substantiate the need to apply international legal standards in the transportation of animals in Ukraine as well as in the European Union. Research methods: comparative law, system-structural and functional. Results: the author considers the peculiarities of the legal regulation of animal transportation by air in Ukraine and clarifies the existence of shortcomings in the procedure for regulating this issue in Ukraine on the example of international legal standards. Discussion: in recent years, society has increasingly paid attention to the protection of animals from cruelty. Trends in ethical, moral, and legal norms of humane treatment of animals are consolidated. There is currently an acute problem with the safe transport of animals. Although domestic legislation has a number of regulations on the rules and standards of transportation of animals, there are still cases where the transportation of animals by air (rail, road) leads to injury or death of animals during their transportation. There are a number of problematic issues at the legislative level and in practice regarding the transportation of animals, which allows Ukraine in the framework of integration with the European Union (hereinafter - the EU), to harmonize domestic legislation with EU law and ratify and implement European standards in this area. It is proposed to consider a single standard that will regulate the transportation of animals by air. The author notes that the legal regulation of the transportation of animals by air is sufficiently provided at the state level, but still airlines supplement their requirements. This leads to the creation of a single standard for safer and more comfortable flight of animals.